An evidenced-based perspective on the validity of attention-deficit/hyperactivity disorder in the context of high intelligence. (December 2016) - Rommelse, Nanda; van der Kruijs, Marieke; Damhuis, Jochem; Hoek, Ineke; Smeets, Stijn; Antshel, Kevin M.; Hoogeveen, Lianne; Faraone, Stephen V.
Highlights: ADHD is a valid disorder in the context of high IQ. Hyperactivity may possibly be a less specific pathology marker in high IQ. ADHD and IQ are negatively correlated on nearly all phenotypic and cognitive constructs. IQ should be explored as potential moderator in ADHD research and clinical practice. Abstract: The validity of Attention-Deficit/Hyperactivity Disorder (ADHD) in individuals with high intelligence is disputed, since high intelligence may 'mimic' the symptoms of ADHD in the absence of the specific pathophysiological pathways for ADHD. Conversely, increased risk of a missed ADHD diagnosis may occur due to compensatory strategies in the highly intelligent individual. A systematic literature review was performed including cognitive and behavioral studies, addressing a specific set of criteria for validating ADHD in the context of high intelligence. Albeit limited in number, available results suggest that ADHD is a valid construct in the context of high intelligence, showing characteristic clinical features (except possibly for hyperactivity being a less specific pathology marker), course and outcome and a characteristic response to treatment. Importantly, ADHD and IQ are negatively correlated on nearly all phenotypic and cognitive constructs, underlining the need for taking IQ into account as potential moderator in ADHD studies and more systematically studying ADHD in the high intelligent population.